Multicomponent chemistry in the synthesis of carbonic anhydrase inhibitors. (4th November 2016) - Kalinin, Stanislav; Supuran, Claudiu T.; Krasavin, Mikhail
Abstract: Carbonic anhydrase inhibitors (CAIs) are of growing interest since various isoforms of the enzyme are identified as promising drug targets for treatment of disease. The principal drawback of the clinically used CAIs is the lack of isoform selectivity, which may lead to observable side effects. Studies aiming at the design of isoform-selective CAIs entail generation and biological testing of arrays of compounds, which is a resource- and time-consuming process. Employment of multicomponent reactions is an efficient synthetic strategy in terms of gaining convenient and speedy access to a range of scaffolds with a high degree of molecular diversity. However, this powerful tool appears to be underutilized for the discovery of novel CAIs. A number of studies employing multicomponent reactions in CAI synthesis have been reported in literature. Some of these reports provide inspiring examples of successful use of multicomponent chemistry to construct novel potent and often isoform-selective inhibitors. On critical reading of several publications, however, it becomes apparent that for some chemical series designed as CAIs, the desired inhibitory properties are only assumed and never tested for. In these cases, the biological profile is reported based on the results of phenotypical cellular assays, with no correlation with the intended on-target activity. Present review aims at critically assessing the current literature on the multicomponent chemistry in the CAI design.